Synthesis of gold nanoparticles coated with glucose oxidase using PVP as passive adsorption linkage - Santos-Santos, I. J.; Zamora-Justo, J. A.; Vázquez-Martínez, G. R.; Cabrera-Sierra, R.; Balderas-López, J. A. (Frontiers in Nanotechnology, 2024)
Gold nanoparticles (AuNPs) have great potential as biosensors for glucose detection due to their high sensitivity, as well as their extraordinary physical and chemical properties that improve compatibility with different biorecognition molecules, such as glucose oxidase (GOx). In this work the D-glucose quantification was determined by using the traditional technique based on biochemical reaction of GOx and AuNPs functionalized with polyvinylpirrolidone (PVP) polymer and the enzyme. The AuNPs-PVP-GOx nanocomplexes were characterized by ultraviolet-visible (UV-Visible), Infrared (FTIR), and Raman spectroscopies, as well as scanning electron microscopy (SEM), Z potential, dynamic light scattering (DLS), and thermogravimetry analysis (TGA). In general, these techniques showed significant differences after each functionalization stage with PVP and GOx, for instance it was observed: the presence of different functional groups, an increase of hydrodynamic diameter from 48.60 to 198.77 nm, a shift of the band absorption to larger wavelength, a change in the surface potential and weight loss, and in the morphology of the nanocomplex, which confirm the functionalization. In addition, the enzymatic activity of the AuNPs-PVP-GOx was confirmed through the detection of triiodide ions by UV-Visible spectrophotometry, coming from the oxidation reaction of iodide ions in the presence of H2O2. Furthermore, the nanocomplex synthesized by passive adsorption was evaluated as a possible biosensor for the quantification of D-glucose using a colorimetric assay, obtaining greater sensitivity than the traditional method. These findings indicate that PVP can be used as a linkage medium between AuNPs and GOx, which in turn can be used as a biosensor for the detection of D-glucose at low concentrations in biological fluids.